The Political Law on Coal Mining in the Fulfilment of People's Welfare in Indonesia - Irsan Irsan; Meria Utama (Faculty of Law, Sriwijaya University, Indonesia, 2019)
The main issue of this research is how the political law on coal mining to manifest the people's prosperity in Indonesia based on the sustainable development principle. Using normative research with interdisciplinary research approaches such as law and sociological approach, it gains some results: firstly, in the legal issue, Indonesian government should comply with the Article 33 of the 1945 Constitution, as an economic system aimed in realizing people's sovereignty in the economic field. Secondly, some regulations related to coal mining still have some loopholes. As a result, it needs evaluation in the field of legal structure to enforce the rule of law based on the communities’ existing values as the reflection of Pancasila and the 1945 Constitution. Thirdly, the control of the state in the coal utilization and a new balancing in national policy management based on the sustainable development are necessary where the objectives of coal exploitations in mining are not only to pursue economic gain but also to have equal responsibilities to the social and the environment